The Effect of Self – Repair Strategies on Students’ Speaking Skills in Eleventh Grade at SMA Negeri 2 Bangli - Witya Arindrayanthi Risa; Ni Wayan Satri Adnyani; Ni Ketut Riska Dewi Prawita (Indo Publishing, 2026)
This study aimed to determine whether there was a significant effect of self-repair strategies on students’ speaking skills at the eleventh grade of SMA Negeri 2 Bangli. This study used a quantitative approach with a quasi-experimental research design. The participnts consisted of 68 students divided into two groups, The research instruments used in this study was speaking tests. The data were collected through pre-test, treatment, and post-test. The data were analyzed using descriptive statistical analysis and inferential statistical analysis through an independent sample t-test. The findings showed that the mean score of the experimental group in the post-test was higher (M = 85.15) than the control group (M = 76.32). The result of the independent sample t-test showed a t-value of 13.637 with a significance value lower than 0.05, indicating that there was a significant difference between the experimental group and the control group after the treatment. These findings related to Constructivism theory. Therefore, self-repair strategies were effective in improving students’ speaking skills at the eleventh grade of SMA Negeri 2 Bangli.